2013
DOI: 10.1186/1471-2458-13-943
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition among HIV positive women in Humera hospital, Tigray, Ethiopia, 2013: antiretroviral therapy alone is not enough, cross sectional study

Abstract: BackgroundIn Ethiopia, undernutrition among women on antiretroviral therapy has been a major challenge to achieve the full impact of intervention. Twenty seven percent and 17% of reproductive age Ethiopian women are chronically malnourished and anemic, respectively. Most studies to examine risk factors have been limited to the general population and ART-naive HIV-positive women, making it difficult to generalize findings to ART-treated HIV-positive women. The objectives of this study were thus to assess nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 11 publications
9
38
4
Order By: Relevance
“…Level of malnutrition in this study was 43.02%, this result is the line with study done in Thailand which is 41.3% [6] and also similar with a study done in Tigray Ethiopia which is 42.3% [30]. Higher than study conducted at Dilla (12.3%), Gondar (25.5%) and Bihar Dar [31][32][33]. The difference might be due to different socio-economic status, stages of HIV, and awareness levels among the study participants.…”
Section: Discussionsupporting
confidence: 90%
“…Level of malnutrition in this study was 43.02%, this result is the line with study done in Thailand which is 41.3% [6] and also similar with a study done in Tigray Ethiopia which is 42.3% [30]. Higher than study conducted at Dilla (12.3%), Gondar (25.5%) and Bihar Dar [31][32][33]. The difference might be due to different socio-economic status, stages of HIV, and awareness levels among the study participants.…”
Section: Discussionsupporting
confidence: 90%
“…Mulu et al noted a much higher prevalence [46.8%] in comparison to the findings of the current study (Mulu, Hamza, & Alemseged, 2016). Hadgu et al reported a prevalence of 42.3% (Hadgu, Worku, Tetemke, & Berhe, 2013). This is way higher than the findings of the current study.…”
Section: Discussioncontrasting
confidence: 76%
“…Of the total 20 articles, more than one third of studies were conducted in Amhara regional state health institutions [2, 14, 18, 20, 23, 24, 26, 28]; four studies in Addis Ababa health institutions [13, 16, 21, 22]; four studies at South Nations Nationalities and peoples of Ethiopia national regional state (SNNP) [3, 15, 17, 34]; one study at Oromia national regional state [19], one study at Gambella national regional state [27], one study at Tigray regional national state [35] and one study at Dire Dawa town administration of Ethiopia [25]. …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the study designs, 13 studies [3, 13, 15, 17–20, 25–28, 34, 35] and the remaining seven were cross sectional and cohort studies respectively. After critical appraisal of each articles based on JBI-MAStARI, both in peer and independently, they scored in the range of 5-up to 8 out of 9 values (see Table 1).…”
Section: Resultsmentioning
confidence: 99%